Optical Superresolution Sensing of a Trapped Ion’s Wave Packet Size - Drechsler, Martin; Wolf, Sebastian; Schmiegelow, Christian T.; Schmidt-Kaler, Ferdinand (Physical Review Letters, 2021)
We demonstrate superresolution optical sensing of the size of the wave packet of a single trapped ion. Our method extends the well-known ground state depletion (GSD) technique to the coherent regime. Here, we use a hollow beam to strongly saturate a coherently driven dipole-forbidden transition around a subdiffraction limited area at its center and observe state dependent fluorescence. By spatially scanning this laser beam over a single trapped ion, we are able to measure the wave packet sizes of cooled ions. Using a depletion beam waist of we reach a spatial resolution which allows us to determine a wave packet size of 39(9) nm for a near ground state cooled ion. This value matches an independently deduced value of 32(2) nm, calculated from resolved sideband spectroscopy measurements. Finally, we discuss the ultimate resolution limits of our adapted GSD imaging technique in view of applications to direct quantum wave packet imaging.
Created from Fastlane, Scopus look-up